Redescription of Nigrobaetis rhithralis (Soldán & Thomas, 1983) (Ephemeroptera: Baetidae) - Godunko, Roman J.; Martynov, Alexander V.; Gattolliat, Jean-Luc (Zootaxa, 2018)
Nigrobaetis rhithralis (Soldán & Thomas, 1983) is completely redescribed at larval and imaginal stages of both sexes based on the type material. This species and the closely related Palaearctic species Nigrobaetis digitatus (Bengtsson, 1912) were compared to clarify their relationships. Several new distinguishing characters useful for separation of these two species are proposed and discussed; they may be further used to distinguish cryptic species within the genus Nigrobaetis Novikova & Kluge, 1987.